The importation of Late Rom an red slip wares into Bosporus (Kerch) - Smokotina, Anna (Rei Cretariae Romanae Fautorum Acta, 2022)
Recent excavations in Kerch (ancient Pantikapaion, Bosporus) revealed new archaeological complexes of the Late Roman period. There are four manufacturing groups of the red slip ware in the second half of the 4th to the first half of the 7th centuries AD: Pontic Red Slip, African Red Slip, Late Roman C / Phocean Red Slip and Late Roman Light-Colored. In the late 4th–early 6th century the Black Sea regional trade played the main role and Bosporus had the closest relations with the South Pontic centers. PRS ware prevailed in Bosporan complexes and only isolated fragments of other red slip ware groups reached the city during this period. The import from the Mediterranean centers sharply increased from the second quarter of the 6th century. LRC/PhRS vessels in Bosporan complex reached on average approximately 70 %. However after the middle of the 6th century the Phocean import drastically curtailed. Currently Bosporan complexes of the first half of the 7th century have not yet been discovered. Nevertheless rare imported finds in Bosporus indicate a continuation of some traditional trade relations and some red slip ware supplies to the city from the Mediterranean centers at least until the middle of the 7th century.